Association between physical multimorbidity and sleep problems in 46 low- and middle-income countries. (June 2022) - Smith, Lee; Shin, Jae Il; Jacob, Louis; Schuch, Felipe; Oh, Hans; Tully, Mark A; López Sánchez, Guillermo F; Veronese, Nicola; Soysal, Pinar; Yang, Lin; Butler, Laurie; Barnett, Yvonne; et al.
Highlights: Results are reported from a large study, with a sample of 237, 023 individuals aged 18 years and over (mean age 38.4 years; 49.2% men). Multimorbidity was associated with substantially increased odds for sleep problems. Influential factors were pain (24.0%), anxiety (21.0%), depression (11.2%), and stress (10.4%). Abstract: Background: Little is known about the association between multimorbidity (i.e., two or more chronic conditions) and sleep problems in the general adult populations of low- and middle-income countries (LMICs). Thus, we aimed to assess this association among adults from 46 LMICs, and to quantify the extent to which anxiety, depression, stress, and pain explain this association. Methods: Cross-sectional, predominantly nationally representative, community-based data from the World Health Survey were analyzed. Nine chronic physical conditions (angina, arthritis, asthma, chronic back pain, diabetes, edentulism, hearing problems, tuberculosis, visual impairment) were assessed. To be included in the analysis, sleep problems had to have been experienced in the past 30 days and to have been severe or extreme; they included difficulties falling asleep, waking up frequently during the night or waking up too early in the morning. Multivariable logistic regression and mediation analyses were conducted to explore the associations. Results: Data on 237, 023 individuals aged ≥18 years [mean (SD) age 38.4 (16.0) years; 49.2% men] were analyzed. Compared with no chronic conditions, having 1, 2, 3, and ≥4 conditions was associated with 2.39 (95%CI=2.14, 2.66), 4.13 (95%CI=3.62, 4.71), 5.70 (95%CI=4.86, 6.69), and 9.99 (95%CI=8.18, 12.19) times higher odds for sleep problems. Pain (24.0%) explained the largest proportion of the association between multimorbidity and sleep problems, followed by anxiety (21.0%), depression (11.2%), and stress (10.4%). Conclusions: Multimorbidity was associated with a substantially increased odds for sleep problems in adults from 46 LMICs. Future studies should assess whether addressing factors such as pain, anxiety, depression, and stress in people with multimorbidity can lead to improvement in sleep in this population.